Evidence Based Updating of HbA1c Targets: Global Guidelines forGlycemic Control in Type 2 Diabetes Mellitus - Khazaal, Faris AK; Abdulaziz, Lewai S (AL-Kindy College Medical Journal, 2015)
Background:Measurement of hemoglobin A1c (A1C) is a renowned tactic for gauging long-term glycemic control, and exemplifies an outstanding influence to the quality of care in diabetic patients.The concept of targets is open to criticism; they may be unattainable, or limit what could be attained, and in addition they may be economically difficult to attain. However, without some form of targeted control of an asymptomatic condition it becomes difficult to promote care at allObjectives: The present article aims to address the most recent evidence-based global guidelines of A1C targets intended for glycemic control in Type 2 Diabetes Mellitus (T2D).Key messages:Rationale for Treatment Targets of A1C includesevidence for microvascular and macrovascular protectionand changes in quality of life. More or less stringent A1C goals may be appropriate for individual patients, andgoals should be individualized based on:duration of diabetes, age/life expectancy, comorbid conditions, CVD or advanced microvascular complications,hypoglycemia unawareness, and individual patient considerations